La liberté est-elle divisible? Comment rapprocher les concepts de mission et de sécurité dans une politique étrangère américaine - Nolan, Cathal (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1991)
This article seeks to outline the complex pattern of liberty and national security in international relations through a survey of the historical relationship between those concerns in the foreign policy of what is still the world's most important democratic country, the United States. This study is not a history per se of American diplomacy concerning this cluster of issues, although it is historical in approach. Nor is it directly concerned with an on-going theoretical debate over whether or not democracies are inherently more peaceful than other types of states, despite drawing upon elements of that debate and having implications for it. Instead, what is presented here is an interpretive survey of the importance in U.S. foreign policy of a set of key ideas about international order — specifically, the attempt to resolve ideas of "American mission " with the requirements of security, through increasingly active linkage of U.S. national security to the internal character of foreign regimes. It then explores how that tension became manifest in two policy settings : the United Nations, one of America's major multilateral relationship s, and the Soviet Union, its principal bilateral relationship. In short, this study is concerned with governing ideas in American diplomacy; with how such ideas arise and are sustained or challenged; with how they have been disseminated among allies (and even adversaries) ; and the implications of the reality that the United States have succeeded in imbedding these notions in the structures of the international System. The essay concludes with what should prove a controversial, qualified approval of the new 'liberal realism' evident in American foreign policy in the early 1990s.